RECONSTRUCTION OF THE NETWORK PUMPING UNIT OF THE CHAUNSKAYA ORGANIZATION FOR THE DISTRIBUTION OF HEAT AND ELECTRICITY USING A FREQUENCY-CONTROLLED DRIVE - A.Yu. Zaika (Zenodo, 2023)
The article presents the results of a study of the Chaun thermal power plant, located in the city of Pevek, Chukotka Autonomous Okrug, and assesses the feasibility of introducing a frequency-controlled drive of the network pumping unit of the Chaun organization for the distribution of heat and electricity (Chukotenergo). The results of measurements of the pumping unit for the heating period are given. The climatological data for the city of Pevek are presented. The selection of network pumps, electric motors, requirements for an automated electric drive and for the automation system of a pumping unit was carried out, taking into account the expected reduction in the consumption of thermal energy and coolant from the Chaun organization for the distribution of heat and electricity.